Glass ceramic, preparation method thereof and glass product
By reasonably proportioning the glass components and preparation treatment, microcrystalline glass with low expansion coefficient, high transparency and high mechanical strength was prepared, which solved the problem of the reduction of strength of traditional microcrystalline glass at high temperatures and is suitable for a variety of high-temperature environment applications. .
Patent Information
- Application Number
- CN202411285510.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The traditional zero-expansion transparent microcrystalline glass has a high expansion coefficient of 50℃~750℃, which leads to a decrease in strength after crystallization, which is prone to cracking, limiting its application range.
By reasonably proportioning the components of SiO2, Al2O3, Li2O, MgO, ZnO, TiO2, ZrO2, P2O5 and B2O3, microcrystalline glass with β-quartz solid solution was prepared, and nucleation and crystallization were performed to control the β-quartz solid solution. Crystality and grain size reduce the expansion coefficient and stress concentration of the matrix glass.
A microcrystalline glass with low expansion coefficient, high transparency and high mechanical strength is achieved, with a thermal expansion coefficient of 0±1×10-7/K, a transmittance of more than 85%, a ball-resistance resistance height of more than 90cm, and an annular pressure strength of more than 2760N.
Smart Images

Figure CN119161106A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of glass technology, and in particular to a microcrystalline glass and a preparation method thereof, and a glass product. Background Art
[0002] At present, most zero-expansion glass-ceramic products use the lithium aluminum silicate system (Li2O-Al2O3-SiO2), whose main crystalline phases are transparent low-expansion β-quartz solid solution and milky white opaque low-expansion β-spodumene solid solution.
[0003] Transparent zero expansion can be achieved by adjusting the ratio of β-quartz solid solution and residual glass phase in glass-ceramics. However, the expansion coefficient of the precipitated β-quartz solid solution is significantly lower than that of the matrix glass, which will cause circumferential tensile stress in the residual glass phase around the β-quartz solid solution, easily causing stress concentration, significantly reducing the overall strength of the glass-ceramics, and even causing cracking in severe cases. The expansion coefficient of the matrix glass of traditional zero-expansion transparent glass-ceramics is relatively high, and the expansion coefficient at 50℃~750℃ is generally greater than 40×10 -7 / K, which leads to a significant decrease in the strength of the microcrystalline glass after crystallization, seriously restricting its application scope.
[0004] Therefore, traditional glass-ceramics still needs to be improved. Summary of the invention
[0005] Based on this, one or more embodiments of the present application provide a microcrystalline glass with low expansion coefficient, high transparency and high mechanical strength, a preparation method thereof, and a glass product. The technical solution includes:
[0006] According to a first aspect of an embodiment of the present application, a glass-ceramic is provided, comprising the following components by mass percentage:
[0007] SiO255wt%~66wt%, Al2O321wt%~28wt%, Li2O 1wt%~4wt%, MgO 1wt%~5wt%, ZnO 0~1.9wt%, TiO20~4wt%, ZrO22wt%~6wt%, P2O51wt%~6wt% and B2O30~3wt%;
[0008] Among them, the mass percentage of TiO2 is a, the mass percentage of ZrO2 is b, the mass percentage of P2O5 is c, the mass percentage of B2O3 is d, and they satisfy 4wt%≤a+b+c+d≤8wt%;
[0009] The mass percentage of ZnO is x, the mass percentage of MgO is y, and x / y≤1 is satisfied.
[0010] In one of the embodiments, the microcrystalline glass satisfies 4.6wt%≤a+b+c+d≤9wt%.
[0011] In one of the embodiments, the microcrystalline glass satisfies x / y≤0.7.
[0012] In one embodiment, the microcrystalline glass comprises the following components by mass percentage:
[0013] SiO260wt%~66wt%, Al2O322wt%~26wt%, Li2O 1wt%~3wt%, MgO 1wt%~5wt%, ZnO 0~1.9wt%, TiO20~2wt%, ZrO22wt%~6wt%, P2O51wt%~4wt% and B2O30~2.5wt%.
[0014] In one embodiment, the crystal phase of the glass-ceramics includes β-quartz solid solution.
[0015] In one embodiment, the microcrystalline glass satisfies at least one of the following conditions (1) to (2):
[0016] (1) The crystallinity of the β-quartz solid solution is greater than or equal to 47%; and
[0017] (2) The grain size of the β-quartz solid solution is 20nm~60nm.
[0018] According to a second aspect of the embodiments of the present application, a method for preparing glass-ceramics is provided, comprising the following steps:
[0019] Providing raw materials according to the above-mentioned components of the glass-ceramics, and mixing the raw materials to prepare a mixture;
[0020] melting the mixture to prepare molten glass;
[0021] The glass liquid is shaped, and subjected to nucleation treatment and crystallization treatment in sequence to obtain the microcrystalline glass.
[0022] In one embodiment, the temperature of the nucleation treatment is 640° C. to 800° C., and the treatment time is 2 h to 12 h.
[0023] In one embodiment, the crystallization treatment temperature is 780° C. to 1000° C., and the treatment time is 0.5 h to 4 h.
[0024] According to a third aspect of an embodiment of the present application, a glass product is provided, comprising the above-mentioned glass-ceramics or glass-ceramics prepared by the above-mentioned method for preparing glass-ceramics.
[0025] Compared with the traditional technology, this application has the following beneficial effects:
[0026] The present application achieves a reasonable ratio of raw material components so that the raw materials cooperate and work synergistically with each other, thereby precipitating a β-quartz solid solution with fine and uniform grain size, and effectively reducing the expansion coefficient of the matrix glass, thereby reducing stress concentration during the crystallization process; ultimately, microcrystalline glass with a low thermal expansion coefficient, high transparency and high mechanical properties is prepared. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0028] Figure 1 This is the XRD diagram of the microcrystalline glass prepared in Example 18 of the present application. DETAILED DESCRIPTION
[0029] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.
[0031] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.
[0032] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.
[0033] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0034] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1 to 10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all sub-ranges included therein.
[0035] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0036] In the present application, %(w / w) and wt% both represent weight percentage, %(v / v) refers to volume percentage, and %(w / v) refers to mass volume percentage.
[0037] In a first aspect of the present application, a glass-ceramic is provided, comprising the following components, by mass percentage: SiO2 55wt%~66wt%, Al2O3 21wt%~28wt%, Li2O 1wt%~4wt%, MgO 1wt%~5wt%, ZnO 0~1.9wt%, TiO2 0~4wt%, ZrO2 2wt%~6wt%, P2O5 1wt%~6wt% and B2O3 0~3wt%;
[0038] Among them, the mass percentage of TiO2 is a, the mass percentage of ZrO2 is b, the mass percentage of P2O5 is c, the mass percentage of B2O3 is d, and they satisfy 4wt%≤a+b+c+d≤8wt%;
[0039] The mass percentage of ZnO is x, the mass percentage of MgO is y, and x / y≤1 is satisfied.
[0040] In the present application, the mass percentage of SiO2 is "55wt%~66wt%", which means the minimum and maximum values in the range of 55wt%~66wt%, and each value between the minimum and maximum values. Specifically including but not limited to the point values in the embodiment and the following point values: 55wt%, 56wt%, 57wt%, 58wt%, 59wt%, 60wt%, 61wt%, 62wt%, 63wt%, 64wt%, 65wt% or 66wt%; or a range composed of any two of these values, such as: 58wt%~63wt%.
[0041] In some optional embodiments, the mass percentage of SiO2 is 60wt%~66wt%; further, the mass percentage of SiO2 is 60wt%~64.5wt%; further, the mass percentage of SiO2 is 64.5wt%.
[0042] SiO2 is an important oxide for glass forming and can be used to stabilize the network structure of glass and glass ceramics. In glass and glass ceramics, SiO2 is the main oxide for forming glass from base glass and one of the main oxides of the main crystal phase. It can be used to stabilize the network structure of glass and glass ceramics and the formation of the main crystal phase of β-quartz solid solution. Controlling the mass percentage of SiO2 within the above-mentioned specific range can, on the one hand, reduce the melting temperature of microcrystalline glass, reduce the production difficulty, unit energy consumption and carbon emissions; on the other hand, it is also conducive to the precipitation of β-quartz solid solution crystal phase.
[0043] In the present application, the mass percentage of Al2O3 is "21wt%~28wt%", that is, the minimum and maximum values of the range of 21wt%~28wt%, and each value between the minimum and maximum values. Specifically including but not limited to the point values in the embodiment and the following point values: 21wt%, 21.5wt%, 22wt%, 22.5wt%, 23wt%, 23.5wt%, 24wt%, 24.5wt%, 25wt%, 25.5wt%, 26wt%, 26.5wt%, 27wt%, 27.5wt% or 28wt%; or a range composed of any two of these values, such as: 22.6wt%~26.8wt%.
[0044] In some optional embodiments, the mass percentage of Al2O3 is 22wt%~26wt%; further, the mass percentage of Al2O3 is 25wt%~26wt%; further, the mass percentage of Al2O3 is 25.5wt%.
[0045] Al2O3 can also be used to stabilize the network structure of glass and improve the mechanical properties and chemical durability of glass. At the same time, Al2O3 is also one of the main oxides of the main crystal phase of β-quartz solid solution. In order to ensure the formation of the main crystal phase and the grain size, its content needs to be controlled within a specific range. However, the melting temperature of Al2O3 is relatively high. As a network intermediate, the viscosity of the glass can be controlled by adjusting its content.
[0046] In the present application, the mass percentage of Li2O is "1wt%~4wt%, that is, the minimum and maximum values of the range of 1wt%~4wt%, and each value between the minimum and maximum values. Specifically including but not limited to the point values in the embodiment and the following point values: 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2.wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt%, 3.6wt%, 3.7wt%, 3.8wt%, 3.9wt% or 4wt%; or a range composed of any two of these values, such as: 1.5wt%~3.5wt%.
[0047] In some optional embodiments, the mass percentage of Li2O is 1wt%~3wt%; further, the mass percentage of Li2O is 1wt%~2wt%; further, the mass percentage of Li2O is 1.3wt%.
[0048] Alkali metal oxide Li2O has the function of lowering the melting temperature and improving the ion exchange capacity. It is also one of the components of the β-quartz solid solution crystal phase and is indispensable. At the same time, it has the characteristics of small ion radius and strong field strength, and is easy to accumulate in the glass network structure, which is conducive to the nucleation and growth of lithium-containing crystal phase. Controlling its content within a specific range can provide sufficient power for the precipitation of the target crystal phase and make the glass network structure dense, thereby reducing the thermal expansion coefficient of the matrix glass and enhancing the strength of the microcrystalline glass.
[0049] In addition, lithium raw materials are expensive, and controlling the Li2O content within a specific range can effectively reduce the raw material cost of microcrystalline glass.
[0050] In the present application, the mass percentage of MgO is "1 wt% to 5 wt%", that is, it can take a minimum value and a maximum value in the range of 1 wt% to 5 wt%, and every value between the minimum value and the maximum value. Specifically, it includes but is not limited to the point values in the embodiments and the following point values: 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt%, 3.6wt%, 3.7wt%, 3.8wt%, 3.9wt%, 4wt%, 4.1wt%, 4.2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt% or 5wt%; or a range composed of any two of these values, such as: 1.8wt%~4.5wt%.
[0051] In some optional embodiments, the mass percentage of MgO is 2wt%~5wt%; further, the mass percentage of MgO is 2wt%~4wt%; further, the mass percentage of MgO is 3.5wt%.
[0052] In the present application, the mass percentage of ZnO is "0-1.9wt%", that is, the minimum and maximum values of the range of 0-1.9wt%, and each value between the minimum and maximum values. Specifically including but not limited to the point values in the embodiment and the following point values: 0wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt% or 1.9wt%; or a range composed of any two of these values, such as: 0.5wt%-1.5wt%.
[0053] In some optional embodiments, the mass percentage of ZnO is 0-1.5wt%; further, the mass percentage of ZnO is 0.2wt%-1wt%; further, the mass percentage of ZnO is 0.6wt%.
[0054] It is understandable that adding appropriate alkaline earth metal oxides MgO and ZnO to the glass components is beneficial to reducing the high temperature viscosity of the base glass, modifying the glass structure, and improving the strength and chemical stability of the base glass. Controlling the MgO content within the above-mentioned specific range can reduce the high temperature viscosity of the melt of the base glass, thereby reducing its melting difficulty; and it is not easy to precipitate impurities such as periclase, thereby increasing the transparency of the microcrystalline glass and reducing the thermal expansion coefficient. ZnO ions have a high field strength accumulation effect in the glass melt, and a small amount of addition is conducive to the precipitation of the target crystal phase.
[0055] In the present application, the mass percentage of TiO2 is "0-4wt%", which means that it can take a minimum value and a maximum value in the range of 0-4wt%, as well as every value between the minimum value and the maximum value. Specifically, it includes but is not limited to the point values in the embodiments and the following point values: 0wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt%, 3wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt%, 3.6wt%, 3.7wt%, 3.8wt%, 3.9wt% or 4wt%; or a range composed of any two of these values, such as: 0.5wt%~3.5wt%.
[0056] In some optional embodiments, the mass percentage of TiO2 is 0-2wt%; further, the mass percentage of TiO2 is 0-1wt%; further, the mass percentage of TiO2 is 0.2wt%.
[0057] In the present application, the mass percentage of ZrO2 is "2wt%~6wt%", that is, the minimum and maximum values in the range of 2wt%~6wt%, and each value between the minimum and maximum values. Specifically including but not limited to the point values in the embodiment and the following point values: 2wt%, 2.2wt%, 2.4wt%, 2.6wt%, 2.8wt%, 3wt%, 3.2wt%, 3.4wt%, 3.6wt%, 3.8wt%, 4wt%, 4.2wt%, 4.4wt%, 4.6wt%, 4.8wt%, 5wt%, 5.2wt%, 5.4wt%, 5.6wt%, 5.8wt% or 6wt%; or a range composed of any two of these values, such as: 2.7wt%~5.5wt%.
[0058] In some optional embodiments, the mass percentage of ZrO2 is 2wt%~4wt%; further, the mass percentage of ZrO2 is 2wt%~3wt%; further, the mass percentage of ZrO2 is 2.5wt%.
[0059] In the present application, the mass percentage of P2O5 is "1wt%~6wt%", that is, the minimum and maximum values in the range of 1wt%~6wt%, and each value between the minimum and maximum values. Specifically including but not limited to the point values in the embodiment and the following point values: 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, 2wt%, 2.2wt%, 2.4wt%, 2.6wt%, 2.8wt%, 3wt%, 3.2wt%, 3.4wt%, 3.6wt%, 3.8wt%, 4wt%, 4.2wt%, 4.4wt%, 4.6wt%, 4.8wt%, 5wt%, 5.2wt%, 5.4wt%, 5.6wt%, 5.8wt% or 6wt%; or a range composed of any two of these values, such as: 2.7wt%~5.5wt%.
[0060] In some optional embodiments, the mass percentage of P2O5 is 1wt%~4wt%; further, the mass percentage of P2O5 is 1wt%~2.5wt%; further, the mass percentage of P2O5 is 1.6wt%.
[0061] TiO2, ZrO2 and P2O5 are added as nucleating agents to improve the crystallization ability of the glass and the liquidus temperature during the formation process, thereby improving the crystallization ability of the lithium aluminum silicon system matrix glass.
[0062] β-quartz solid solution glass-ceramics has a low crystallization tendency and a high crystallization barrier. Generally, it is necessary to add TiO2 or more ZrO2 or P2O5 to significantly reduce its crystallization activation energy, promote the precipitation of uniform crystal nuclei in the base glass, and generate the target crystal phase.
[0063] TiO2 has a strong coloring ability and will give the base glass a darker color, so it is not advisable to add too much. Controlling the TiO2 content within a specific range can reduce the thermal expansion coefficient of the base glass, improve the glass strength, make the growth process of the precipitated crystal phase easier to control, and reduce the generation of impurities, thereby improving the comprehensive performance of the microcrystalline glass.
[0064] ZrO2 has a low solubility in the glass and an extremely high melting point, so it is not advisable to add too much. Controlling the content of ZrO2 within a specific range can make the growth process of the precipitated crystal phase easier to control and reduce the generation of impurity phases.
[0065] Adding appropriate P2O5 while adding ZrO2 can effectively increase the solubility of ZrO2 in the glass liquid, which is beneficial to melting; on the other hand, P2O5 itself has the functions of phase separation, grain refinement, and crystallization promotion, which is beneficial to the regulation of the crystallization process of the basic glass. At the same time, controlling the content of P2O5 within a specific range can also help reduce the high-temperature viscosity of the glass.
[0066] In the present application, the mass percentage of B2O3 is "0-3wt%", that is, the minimum and maximum values of the range of 0-3wt%, and each value between the minimum and maximum values. Specifically including but not limited to the point values in the embodiment and the following point values: 0wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt%, 2wt%, 2.1wt%, 2.2wt%, 2.3wt%, 2.4wt%, 2.5wt%, 2.6wt%, 2.7wt%, 2.8wt%, 2.9wt% or 3wt%; or a range composed of any two of these values, such as: 2.7wt%-5.5wt%.
[0067] In some optional embodiments, the mass percentage of B2O3 is 0-2.5wt%; further, the mass percentage of B2O3 is 0wt%-1wt%; further, the mass percentage of B2O3 is 0.3wt%.
[0068] Adding a specific amount of B2O3 helps to lower the melting temperature of the glass and the expansion coefficient of the matrix glass, which is beneficial to improving the strength of the microcrystalline glass; at the same time, it plays an auxiliary role in crystal nucleus growth and grain refinement.
[0069] In the present application, the sum of the mass percentages of ZrO2, TiO2, P2O5 and B2O3 is "4wt%~8wt%, which means that the minimum and maximum values in the range of 4.6wt%~9wt% can be taken, as well as every value between the minimum and maximum values. Specifically including but not limited to the point values in the embodiments and the following point values: 4wt%, 4.2wt%, 4.4wt%, 4.6wt%, 4.8wt%, 5wt%, 5.2wt%, 5.4wt%, 5.6wt%, 5.8wt%, 6wt%, 6.2wt%, 6.4wt%, 6.6wt%, 6.8wt%, 7wt%, 7.2wt%, 7.4wt%, 7.6wt%, 7.8wt% or 8wt%; or a range consisting of any two of these values, such as: 4.5wt%~7.7wt%.
[0070] In some optional embodiments, the sum of the mass percentages of ZrO2, TiO2, P2O5 and B2O3 is 4.6wt%~7.9wt%; further, the sum of the mass percentages of ZrO2, TiO2, P2O5 and B2O3 is 4.6wt%~5wt%; further, the sum of the mass percentages of ZrO2, TiO2, P2O5 and B2O3 is 4.6wt%.
[0071] It can be understood that the mass percentage ratio of ZnO to MgO can be any value between 0 and 1; for example, it can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.
[0072] In some optional implementations, the mass percentage ratio of ZnO to MgO is less than or equal to 0.7, that is, it can take any value between 0 and 0.7.
[0073] In the present application, by limiting the sum of the mass percentages of ZrO2, TiO2, P2O5 and B2O3 within a specific range and limiting the mass percentage ratio of ZnO to MgO within a specific range, the matrix glass can have a lower expansion coefficient, and at the same time, a large number of evenly distributed, nano-sized β-quartz solid solution crystal phases are precipitated, so that the product can ultimately achieve high strength, high transmittance and zero expansion properties.
[0074] It is understandable that in order to speed up the clarification rate of the above components during the melting process, one or more environmentally friendly clarifiers such as SnO2, NaCl, NaNO3, CeO2, etc. can be added to the glass components.
[0075] The microcrystalline glass components of the present application do not contain toxic clarifier components such as arsenic and antimony, and are environmentally friendly.
[0076] In some embodiments, the microcrystalline glass includes the following components, measured by mass percentage: SiO2 60wt%~66wt%, Al2O3 22wt%~26wt%, Li2O 1wt%~3wt%, MgO 1wt%~5wt%, ZnO 0~1.9wt%, TiO2 0~2wt%, ZrO2 2wt%~6wt%, P2O5 1wt%~4wt% and B2O3 0~2.5wt%.
[0077] In some embodiments, the microcrystalline glass includes the following components, measured by mass percentage: SiO2 60wt%~64.5wt%, Al2O3 22wt%~26wt%, Li2O 1wt%~4wt%, MgO 2wt%~4wt%, ZnO 0~1.9wt%, TiO2 0~1wt%, ZrO2 2wt%~4wt%, P2O5 1wt%~2.5wt% and B2O3 0~3wt%.
[0078] In a specific example, the microcrystalline glass includes the following components, by mass percentage: SiO2 64.5wt%, Al2O3 25.5wt%, Li2O 1.3wt%, MgO 3.5wt%, ZnO 0.6wt%, TiO2 0.2wt%, ZrO2 2.5wt%, P2O51.6wt% and B2O3 0.3wt%.
[0079] In some of these embodiments, the crystalline phase of the glass-ceramics includes a β-quartz solid solution.
[0080] In some specific embodiments, the crystallinity of the β-quartz solid solution is greater than or equal to 47%.
[0081] In some specific embodiments, the grain size of the β-quartz solid solution is 20 nm to 60 nm.
[0082] The microcrystalline glass of the present application is prepared by reasonably proportioning the raw material components so that the components cooperate with each other and work synergistically. The transmittance of the microcrystalline glass at a thickness of 4 mm is greater than or equal to 85%, and the thermal expansion coefficient (50°C~750°C) is 0±1×10 -7 / K, resistance to 535g steel ball falling height greater than or equal to 90cm, ROR ring crush strength greater than or equal to 2760N.
[0083] In a second aspect of the present application, a method for preparing glass-ceramics is provided, comprising the following steps S10 to S30.
[0084] Step S10: providing raw materials according to the above-mentioned components of the glass-ceramics, and mixing the raw materials to prepare a mixture;
[0085] Step S20: melting the mixture to prepare molten glass;
[0086] Step S30: shaping the glass liquid, and sequentially performing nucleation treatment and crystallization treatment to obtain microcrystalline glass.
[0087] In some embodiments, in step S20, the melting temperature is 1600° C. to 1700° C., and the melting time is 4 h to 8 h.
[0088] It can be understood that the present application reduces the melting temperature of glass by adjusting the components of glass-ceramics, thereby reducing the difficulty of producing glass-ceramics.
[0089] In some embodiments, in step S30, the temperature of the nucleation treatment is 640° C. to 800° C., and the treatment time is 2 h to 12 h.
[0090] In some embodiments, in step S30, the temperature of the crystallization treatment is 780°C to 1000°C, and the treatment time is 0.5h to 4h.
[0091] In a third aspect of the present application, a glass product is provided, comprising the above-mentioned glass-ceramics or the glass-ceramics prepared by the above-mentioned method for preparing the glass-ceramics.
[0092] The above-mentioned glass products of the present application can meet the high-strength protection requirements of application fields such as stove panels such as induction cookers, electric ceramic stoves and integrated stoves, as well as fire-resistant insulation panels in high-temperature environments such as fireplaces and ovens.
[0093] The glass product of the present application can also be applied to astronomical telescopes, fireproof glass, heat-resistant furnace window glass, high-temperature devices, chemical industry, electronics, navigation, exploration and military fields.
[0094] The present application will be further described below in conjunction with specific examples and comparative examples, but they should not be construed as limiting the scope of protection of the present application. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art.
[0095] Embodiment 1:
[0096] Provide various raw materials according to the glass components recorded in Table 1. After being fully mixed, melt them in a platinum crucible at 1600℃~1700℃ for 4h~8h, and stir them with a platinum stirring paddle. After the stirring paddle is withdrawn, cool down to 1500℃~1600℃, keep warm for 2h to homogenize, and cast them into an iron mold to form a glass block of about 200mm×200mm in size. The mold is preheated to 400℃ before casting. After the glass block hardens, it is immediately transferred to an annealing furnace for annealing, kept warm for 2h, then cooled by 140℃ for 6h, cooled naturally, taken out and set aside.
[0097] The glass components of Examples 2 to 22 and Comparative Examples 1 to 6 are shown in Table 1, and the specific preparation steps are the same as those of Example 1.
[0098] Table 1
[0099]
[0100] In Table 1, “ / ” means that the component is not included.
[0101] The substrate glasses prepared in the above-mentioned Examples 1 to 22 and Comparative Examples 1 to 6 were respectively cut into glass sheets of 200×200×4.3 mm by a Shenyang Kejing STX-1203 wire cutting machine, thinned and polished to about 4 mm by a double-sided grinding and polishing machine, and then edged by a CNC engraving machine. The transmittance in the wavelength range of 380nm to 780nm was tested using a Lambda950 UV-visible spectrophotometer from PerkinElmer, USA, and the thermal expansion coefficient was tested using a German NETZSCH DIL 402 thermal expansion instrument. The results are shown in Table 2.
[0102] Table 2
[0103]
[0104] The base glass prepared in the above Examples 1 to 21 was subjected to nucleation treatment and crystallization treatment according to the parameters shown in Table 3. The equipment used for the treatment was a Nabertherm crystallization furnace. After the glass was crystallized, it was cut, and the cross section was ground and polished for use.
[0105] Table 3
[0106]
[0107] The samples prepared in each embodiment were cut into 50mm×50mm pieces, and their crystalline phase types were tested by Bruker D8 advance X-ray diffractometer, and the proportions of different types of crystalline phases and amorphous phases were calculated by TOPAS software simulation. The transmittance in the wavelength range of 380nm~780nm was tested by Lambda950 UV-visible spectrophotometer produced by PerkinElmer, USA. The thermal expansion coefficient (50℃~750℃) was tested by DIL 402 thermal expansion instrument produced by NETZSCH, Germany. The falling ball impact resistance height was tested by PT-706 drop ball tester produced by Dongguan Puset. The ring compression ROR strength (upper ring φ=16mm, lower ring φ=32mm) was tested by PT-307A universal testing machine produced by Puset. The results are shown in Table 4.
[0108] Figure 1 This is the XRD pattern of the microcrystalline glass prepared in Example 18.
[0109] Table 4
[0110]
[0111] As can be seen from Tables 1 to 4, the components of Comparative Examples 1 to 6 are substantially the same as those of Example 13, except that:
[0112] In Comparative Example 1, the sum of the mass percentages of P2O5, B2O3, ZrO2 and TiO2 is 3.4wt%, which is less than 4wt%, resulting in insufficient crystallization power of the sample, low crystallinity of the sample, and inability to refine the grains, which increases the size of the precipitated crystal phase and reduces the transmittance of the sample, ultimately leading to an excessively high thermal expansion coefficient.
[0113] In Comparative Example 2, the sum of the mass percentages of P2O5, B2O3, ZrO2 and TiO2 is 9.6wt%, which is greater than 8wt%. On the one hand, it leads to an increase in the CTE of the matrix glass; on the other hand, it makes the crystallization process difficult to control, and precipitates a periclase impure phase (crystallinity is 6%), and the grain size of the crystalline phase becomes larger. After crystallization, the transmittance of the microcrystalline glass sample is significantly reduced, and the CTE is increased, which ultimately leads to a significant reduction in the falling ball impact resistance and ring pressure resistance of the microcrystalline glass.
[0114] In Comparative Example 3, the mass percentage of ZnO is 2wt%, and the mass percentage ratio of ZnO to MgO is 1.33, which is greater than 1; the increase in ZnO content and the decrease in MgO content significantly increase the CTE of the matrix glass, affecting the generation of stress concentration during crystallization, and ultimately reducing the falling ball impact and ring compression properties of the microcrystalline glass.
[0115] The mass percentage of ZnO in Comparative Example 4 is 4wt%, which is greater than 1.9wt%. As the ZnO content increases, the CTE of the matrix glass increases significantly, affecting the generation of stress concentration during crystallization. 2+ The high field strength is easy to precipitate zinc-aluminum spinel impurity phase (crystallinity is 3%), which ultimately increases the CTE of the microcrystalline glass and reduces its resistance to falling ball impact and ring pressure.
[0116] The mass percentage of ZrO2 in Comparative Example 5 is 1wt%, which is less than 2wt%. As the ZrO2 content decreases, the crystallization tendency is reduced, and the grain refinement effect during the crystallization process is weakened, resulting in a decrease in crystallinity and an increase in grain size, ultimately reducing the transmittance of the microcrystalline glass, increasing the CTE, and reducing the resistance to falling ball impact and ring pressure.
[0117] In Comparative Example 6, the mass percentage of Li2O is 5wt%, which is greater than 4wt%. With the increase of Li2O content, the structure of the matrix glass becomes looser and the CTE increases significantly. At the same time, the crystallization tendency of the β-spodumene impurity phase (crystallinity of 17%) increases, which greatly reduces the transmittance of the microcrystalline glass, increases the CTE, and reduces the resistance to falling ball impact and ring pressure.
[0118] In summary, the microcrystalline glass containing the above-mentioned specific ratio of the present application has excellent comprehensive properties: transmittance ≥ 85% at a thickness of 4 mm, thermal expansion coefficient (50°C ~ 750°C) 0±1×10 -7 / K, resistance to 535g steel ball falling height ≥90cm, ROR ring pressure ≥2760N.
[0119] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0120] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A glass-ceramic, characterized in that: Calculated by mass percentage, it includes the following components: SiO2 55wt%~66wt%, Al2O3 21wt%~28wt%, Li2O 1wt%~4wt%, MgO 1wt%~5wt%, ZnO 0~1.9wt%, TiO2 0~4wt%, ZrO2 2wt%~6wt%, P2O5 1wt%~6wt% and B2O3 0~3wt%; Among them, the mass percentage of TiO2 is a, the mass percentage of ZrO2 is b, the mass percentage of P2O5 is c, the mass percentage of B2O3 is d, and they satisfy 4wt%≤a+b+c+d≤8wt%; The mass percentage of ZnO is x, the mass percentage of MgO is y, and x / y≤1 is satisfied.
2. The glass-ceramic according to claim 1, characterized in that: The microcrystalline glass satisfies 4.6wt%≤a+b+c+d≤7.9wt%.
3. The glass-ceramic according to claim 1, characterized in that: The microcrystalline glass satisfies x / y≤0.
7.
4. The glass-ceramics according to any one of claims 1 to 3, characterized in that: The microcrystalline glass comprises the following components in percentage by mass: SiO2 60wt%~66wt%, Al2O3 22wt%~26wt%, Li2O 1wt%~3wt%, MgO 1wt%~5wt%, ZnO 0~1.9wt%, TiO2 0~2wt%, ZrO2 2wt%~6wt%, P2O5 1wt%~4wt% and B2O3 0~2.5wt%.
5. The glass-ceramics according to any one of claims 1 to 3, characterized in that: The crystal phase of the glass-ceramics includes β-quartz solid solution.
6. The glass-ceramic according to claim 5, characterized in that: The microcrystalline glass satisfies at least one of the following conditions (1) to (2): (1) The crystallinity of the β-quartz solid solution is greater than or equal to 47%; and (2) The grain size of the β-quartz solid solution is 20nm~60nm.
7. A method for preparing glass-ceramics, characterized in that: The steps include: Providing raw materials according to the components of the glass-ceramics according to any one of claims 1 to 6, and mixing the raw materials to prepare a mixture; melting the mixture to prepare molten glass; The glass liquid is shaped, and subjected to nucleation treatment and crystallization treatment in sequence to obtain the microcrystalline glass.
8. The method for preparing glass-ceramics according to claim 7, characterized in that: The temperature of the nucleation treatment is 640° C. to 800° C., and the treatment time is 2 h to 12 h.
9. The method for preparing glass-ceramics according to claim 7 or 8, characterized in that: The temperature of the crystallization treatment is 780° C. to 1000° C., and the treatment time is 0.5 h to 4 h.
10. A glass product, characterized in that: Including the microcrystalline glass as described in any one of claims 1 to 6 or the microcrystalline glass prepared by the preparation method of the microcrystalline glass as described in any one of claims 7 to 9.
Citation Information
Patent Citations
Crystallizable glass and crystallized glass obtained by crystallizing the same
CN102036926A
Microcrystalline glass, reinforced microcrystalline glass and preparation method thereof
CN111320392A
Li2o-al2o3-sio2-based crystallized glass
CN113710624A
Glass ceramic and preparation method thereof
CN117756411A
Glass ceramic and manufacturing method thereof
CN117865491A
